Cardiac Magnetic Resonance for Ventricular Tachycardia Ablation and Risk Stratification - Roca-Luque, Ivo; Mont-Girbau, Lluis (Frontiers in Cardiovascular Medicine, 2022)
Ventricular tachycardia is the most frequent cause of sudden cardiovascular death in patients with structural heart disease. Radiofrequency ablation is the treatment cornerstone in this population. Main mechanism for structural heart disease-related ventricular tachycardia is re-entry due to presence of slow conduction area within the scar tissue. Electroanatomical mapping with high density catheters can elucidate the presence of both scar (voltage maps) and slow conduction (activation maps). Despite the technological improvements recurrence rate after ventricular tachycardia ablation is high. Cardiac magnetic resonance has demonstrated to be useful to define the location of the scar tissue in endocardium, midmyocardium and/or epicardial region. Furthermore, recent studies have shown that cardiag mangnetic resonance can analyse in detail the ventricular tachycardia substrate in terms of core scar and border zone tissue. This detailed tissue analysis has been proved to have good correlation with slow conduction areas and ventricular tachycardia isthmuses in electroanatomical maps. This review will provide a summary of the current role of cardiac magnetic resonance in different scenarios related with ventricular tachycardia in patients with structural heart disease, its limitations and the future perspectives.